2018
DOI: 10.1113/jp274710
|View full text |Cite
|
Sign up to set email alerts
|

Major influence of a ‘smoke and mirrors’ effect caused by wave reflection on early diastolic coronary arterial wave intensity

Abstract: Coronary arterial wave intensity analysis (WIA) is thought to provide clear insight into upstream and downstream forces on coronary flow, with a large early-diastolic surge in coronary flow accompanied by a prominent backward decompression wave (BDW ), as well as a forward decompression wave (FDW ) and forward compression wave (FCW ). The BDW is believed to arise from distal suction due to release of extravascular compression by relaxing myocardium, while FDW and FCW are thought to be transmitted from the aort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 69 publications
(198 reference statements)
0
9
0
Order By: Relevance
“…On the other hand, although atrial contraction aids ventricular filling, the absence of an atrial inflow valve means that this contraction also generates a BCW that propagates into the systemic/pulmonary veins in a direction that is opposite to mean blood flow ( Hellevik et al, 1999 ; Smiseth et al, 1999 ; Hobson et al, 2007 ; Mynard, 2011 ). Other pump phenomena that generate BCWs in arteries include the active compression of the coronary microvasculature by contracting myocardium ( Davies et al, 2006a ; Mynard et al, 2018 ) and the inflation of an intra-aortic or para-aortic balloon pump ( Kolyva et al, 2009 ; Lu et al, 2012 ).…”
Section: Interpretation Of Wave Patternsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, although atrial contraction aids ventricular filling, the absence of an atrial inflow valve means that this contraction also generates a BCW that propagates into the systemic/pulmonary veins in a direction that is opposite to mean blood flow ( Hellevik et al, 1999 ; Smiseth et al, 1999 ; Hobson et al, 2007 ; Mynard, 2011 ). Other pump phenomena that generate BCWs in arteries include the active compression of the coronary microvasculature by contracting myocardium ( Davies et al, 2006a ; Mynard et al, 2018 ) and the inflation of an intra-aortic or para-aortic balloon pump ( Kolyva et al, 2009 ; Lu et al, 2012 ).…”
Section: Interpretation Of Wave Patternsmentioning
confidence: 99%
“…After a pump has contracted, relaxation causes pressure to fall and therefore generates a decompression wave (sometimes called a ‘suction wave’) ( Figure 7B ). Decompression waves are generated by atrial relaxation ( Smiseth et al, 1999 ; Mynard, 2011 ), release of extravascular pressure on intramyocardial vessels by the relaxing ventricle ( Davies et al, 2006a ; Mynard et al, 2018 ) and deflation of aortic balloon pumps ( Kolyva et al, 2009 ; Lu et al, 2012 ). In the first paper utilizing wave intensity analysis, entitled “What stops the flow of blood from the heart?”, Parker et al (1988) showed that a forward decompression wave (FDW) is primarily responsible for the deceleration of systolic flow in arteries, not a reflected wave as had been widely believed.…”
Section: Interpretation Of Wave Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been speculated that distal reflection is not a confounding factor for the sum-of-squares method ( 5 ), whereas in vitro experiments have shown that wave speed is altered within a stenosis or aneurysm ( 27 ). The influence of wave reflections on wave intensity in coronary vessels was recently investigated ( 28 ). These authors also used a fixed wave speed assessed by the sum-of-squares method.…”
Section: Limitationsmentioning
confidence: 99%